Dental fluorosis in children from Sao Paulo, Southeastern Brazil, 1998-2010 - Narvai, Paulo Capel; Antunes, Jose Leopoldo Ferreira; Frias, Antonio Carlos; Soares, Maria da Candelaria; Marques, Regina Auxiliadora de Amorim; Teixeira, Doralice Severo da Cruz; Frazao, Paulo (Revista de Saúde Pública, 2013)
OBJECTIVE: To assess the trend of dental fluorosis prevalence in 12-year-old children, in the context of exposure to multiple sources of fluoride. METHODS: An analysis was carried out of the trends in prevalence of dental fluorosis in the city of São Paulo, Southeastern Brazil, between 1998 and 2010. The rates of prevalence were calculated for different years (1998, 2002, 2008 and 2010) using secondary data obtained from epidemiological surveys of representative samples of 12-year-old children. Occurrence of fluorosis was assessed in natural light using the Dean index, recommended by the World Health Organization and categorized into normal, questionable, very mild, mild, moderate and severe. In 1998, 125 children were examined, 249 in 2002, 4,085 in 2008 and 231 in 2010. RESULTS: In 1998 the prevalence of fluorosis was 43.8% (95%CI 35.6;52.8) in 2002 it was 33.7% (95%CI 28.2;39.8), it was 40.3% (95%CI 38.8;41.8) in 2008 and 38.1% (95%CI 32.1;44.5) in 2010.The categories very mild + mild totaled 38.4% (95%CI 30.3;47.6) in 1998, 32.1% (95%CI 26.6;38.2) in 2002, 38.0% (95%CI 36.5;39.5) in 2008 and 36.4% (95%CI 30.4;42.7) in 2010. Severe fluorosis was not observed, with statistical significance, in the analyzed period. CONCLUSIONS: The prevalence of dental fluorosis in children from São Paulo can be classified as stationary between 1998 and 2010, both when considering all categories, and when considering only the categories very mild + mild.